Ireland : Eighth Review Under the Extended Arrangement; Staff Report; Staff Supplements; and Press Release on the Executive Board discussion. (IMF Staff Country Reports; Country Report ;, 2012)
The Eighth Review Under the Extended Arrangement discusses Ireland's fiscal policy, financial reforms, economic growth, and employment. The policy implementation of Ireland continued to remain strong, even though the country has been susceptible to global financial shocks. Ireland's steadfast policy implementation has helped access to market funding; however, public debt continued to remain high. The authorities have been finalizing a consolidation package for 2013, with measures that are durable, equitable, and as growth-friendly as possible.